ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIHARGA SAHAM PERUSAHAAN SEKTOR ENERGI - Iqbal Satrya Ponda, (2023)
This study is entitled "Analysis of the Factors Influencing Energy Sector Company Stock Prices". This study examines the effect of the Rupiah/US Dollar exchange rate, profitability, and capital structure on share prices in energy sector companies listed on the Indonesia Stock Exchange in 2018-2021. Thisstudy used 26 companies as samples with a purposive sampling method. Data analysis was performed using Microsoft Excel 2019 and hypothesis testing in this study used Panel Data Regression Analysis with the E-Views 12. The results of the study partially show that, (1) the Exchange Rate doesn't have a significant effect on energy stock prices, (2) Profitability has a significant effecton energy stock prices, (3) Capital Structure doesn't have a significant effect on energy stock prices.